Integrated analysis of miRNAs-mRNAs in skeletal muscle development revealed that novel-miR-766 affects myoblast differentiation and myofiber-type formation in sheep - Gu, Zhenzhen; Duan, WeiWei; Liu, Chenxi; Li, Wenrong; Han, Bin; Liu, Mingjun (Frontiers in Cell and Developmental Biology, 2025)
BackgroundVarious regulators coregulate muscle development in animals. MicroRNAs (miRNAs) are crucial regulators that participate in multiple aspects of myofiber formation. Method: To identify key miRNAs and target genes associated with muscle development, embryos or longissimus dorsi of Chinese Merino sheep were collected for whole-transcriptome sequencing across 11 gestation periods: 26 days (D26), D29, D32, D35, D40, D45, D55, D75, D85, D105, and D135. The functions of key miRNAs and target genes were determined by qRT-PCR, Western blot, dual-luciferase reporter gene assay, and Immunofluorescence staining.ResultsA total of 284 differentially expressed miRNAs (DE-miRNAs) were screened by comparing the transcriptome data across all 11 periods. DE-miRNAs were divided into two developmental stages (stage A and stage B) based on heat map clustering analysis. Functional enrichment analysis revealed that DE-miRNAs in stage A were closely related to myofiber formation, whereas those in stage B were closely related to myofiber growth and maturation. Differential expression and functional enrichment analysis of target genes of DE-miRNAs obtained from stage A revealed the target relationships between 159 DE-miRNAs and 21 differentially expressed target genes associated with myofiber formation. In vitro assays revealed that myoblast differentiation and myotube formation were significantly inhibited by MYH3 knockdown via siMYH3 and that novel-miR-766 targets and decreases the expression of MYH3. In addition, the expression levels of marker genes related to myoblast differentiation and myofiber types were altered after the overexpression and inhibition of novel-miR-766 in sheep myoblasts.DiscussionThis research not only elucidates the core temporal expression patterns of miRNAs but also suggests that novel-miR-766 influences myoblast differentiation and myofiber-type formation. This provides an important theoretical foundation for a deeper understanding of the molecular mechanisms by which miRNAs regulate myofiber development.